Dual citizenship and political participation: migrants in the interplay of united states and colombian politics (2005)
Colombian migrants have naturalized in great numbers following the enactment of Colombian dual citizenship legislation in 1990 and the US immigration reforms of 1990s. Contrary to fears that dual citizenship is detrimental to political engagement and a threat to US democracy, the writer argues that the maintenance of formal ties to their home-country does not result in migrant’s political disengagement from their country of residence. Rather, transnational migrant organizations have played a critical role as agents of political engagement. Colombian dual citizenship has also facilitated migrant’s decision to nationalize in order to prevent the loss of privileges that the us has restricted to those holding citizen status. Contrary to fears that this “instrumental” use of naturalization poses a danger to the nation, the article argues that this motive for naturalization does not necessarily exclude migrant’s interest in political participation and can, instead, be considered an opportunity for inclusion.